2013
DOI: 10.1137/120892921
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Grid-Particle Method for Moving Bodies in 3D Stokes Flow with Variable Viscosity

Abstract: This article presents a new approach for the resolution of large three-dimensional Stokes equations with variable viscosity fluids, coupled with transport equations. After building the model, we will write these equations in the context of highly viscous flows and penalization, in order to consider complex geometries moving in a fluid. From a mathematical point of view, the solutions show nonlinear dynamics. Beside the use of standard tools such as finite differences and staggered grids, we have built a new me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 60 publications
(52 reference statements)
3
44
0
Order By: Relevance
“…Using velocity transforms coefficient and changing the obtained velocity from Step 3 to physical velocity, the total force term ( f lb ) is obtained from Eq. (29). v. F α is computed from Eq.…”
Section: Elastic Forcesmentioning
confidence: 99%
See 2 more Smart Citations
“…Using velocity transforms coefficient and changing the obtained velocity from Step 3 to physical velocity, the total force term ( f lb ) is obtained from Eq. (29). v. F α is computed from Eq.…”
Section: Elastic Forcesmentioning
confidence: 99%
“…They also represent that the windscreen wiper motion and rigid planar motion of cilia would decrease or almost stop the mucus transport. Chatelin and Poncet [29] modeled muco-ciliary clearance by using a hybrid scheme combining an Eulerian scheme for the Stokes equations and a particle method for transport equations. They [29] considered non-Newtonian aspects of viscosity in their method and study different mechanisms of mucus propelling and found dominant factors in muco-ciliary clearance, particularly in the context of cystic fibrosis and aerosol therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The more detailed ones solve the relevant flow equations or some approximation depending on the flow regime and the flow physics that are involved, in realistic geometries. Such methods are the lattice Boltzmann method [9][10][11][12][13], the methods based on particle hydrodynamics [14,15], as well as the standard finite volume methods when applied in complex geometries with moving boundaries [16][17][18]. Lattice Boltzmann models can resolve transport processes in realistic complex geometries, involving complex interactions between species and phases, but are more computational intensive compared to pore network models.…”
Section: Introductionmentioning
confidence: 99%
“…We employed the hybrid particle-mesh method and the vorticity-based subgrid scale model to undertake a numerical flow simulation. The hybrid particle-mesh method is a combination of the vortexin-cell (VIC) method (see [12][13][14][15] and references therein) and the penalization technique [16], which has been developed in recent years (see [17][18][19][20][21][22][23][24] for a review). The hybrid particle-mesh method enables the use of fast and efficient techniques for computing differential operators, thereby enabling large scale simulations.…”
Section: Introductionmentioning
confidence: 99%